The Jurassic of Denmark and Greenland: Early and Middle Jurassic mires of Bornholm and the Fennoscandian Border Zone: a comparison of depositional environments and vegetation - Koppelhus, Eva B.; Nielsen, Lars Henrik; Petersen, Henrik I.; Sørensen, Henning S. (Geological Survey of Denmark and Greenland, 2003)
Suitable climatic conditions for peat formation existed during Early–Middle Jurassic times in the Fennoscandian Border Zone. Autochthonous peat and allochthonous organic matter were depositedfrom north Jylland, south-east through the Kattegat and Øresund area, to Skåne and Bornholm. The increase in coal seam abundance and thickness from north Jylland to Bornholm indicates that the most favourable peat-forming conditions were present towards the south-east. Peat formation and deposition of organic-rich muds in the Early Jurassic coastal mires were mainly controlled by a continuous rise of relative sea level governed by subsidence and an overall eustatic rise. Watertable rise repeatedly outpaced the rate of accumulation of organic matter and terminated peat formationby lacustrine or lagoonal flooding. Organic matter accumulated in open-water mires and in continuously waterlogged, anoxic and periodically marine-influenced mires. The latter conditionsresulted in huminite-rich coals containing framboidal pyrite. The investigated Lower Jurassic seams correspond to peat and peaty mud deposits that ranged from 0.5–5.7 m in thickness, but were generallyless than 3 m thick. It is estimated that on Bornholm, the mires existed on average for c. 1200 years in the Hettangian–Sinemurian and for c. 2300 years in the Late Pliensbachian; the Early Jurassic(Hettangian–Sinemurian) mires in the Øresund area existed for c. 1850 years. Aalenian uplift of the Ringkøbing–Fyn High and major parts of the Danish Basin caused a significant change in the basinconfiguration and much reduced subsidence in the Fennoscandian Border Zone during the Middle Jurassic. This resulted in a more inland position for the Middle Jurassic mires which on occasionenabled peat accumulation to keep pace with, or temporarily outpace, watertable rise. Thus, peat formation was sometimes sustained for relatively long periods, and the mires may have existed for up to 7000 years in the Øresund area, and up to 19 000 years on Bornholm. The combination of the inland ...